Ecological safety during radiological accidents. Analysis and evaluation of emergency situations at radiologically dangerous objects - Kosyrev, S. V.; Matysik, I. A.; Svitnev, I. V. (Journal of Environmental Engineering and Landscape Management, 2005)
The risk of radiological accidents at dangerous objects is minimal when with the help of technical and organizational means it is guaranteed that indoor and outdoor radiation doses are not exceeded. Also, it is necessary to ensure that the quantity of radiological products in the environment doesn't exceed allowed levels both at a normal exploitation of an object and during an accident. In regions with high radiological loads it is necessary to pay enough attention to the safety of dangerous objects in the situations of accidents. An example given in the paper on how to deal with accidents is based on a situation in the Archangelsk region. Analysis was implemented at 23 radiologically dangerous objects. The results of the analysis allowed to determine objects that are dangerous in an ecological sense. Relying on that, methodology of evaluating the situation in the region was created. The main thing is that evaluation of an ecological situation is judged relying on an emergency situation at a radiologically dangerous object. The first step of the methodology preparation is identification of particularly dangerous objects, and modeling of radiological load on an investigated area. The second step of the work is to review the second stage of the methodology which would be dedicated to the analysis and evaluation of emergency situations at radiologically dangerous objects.Article in Russian.Aplinkos apsauga radiacinės avarijos atveju. Avarinių situacijų pavojinguose objektuose analizė ir įvertinimasSantrauka. Avarijų pasekmių rizika radiacijos požiūriu pavojinguose objektuose mažiausia tuo atveju, kai techninėmis bei organizacinėmis priemonėmis yra užtikrinama, kad objekto personalo ir aplinkinių gyventojų vidinės ir išorinės apšvitos dozės nebūtų viršijamos. Taip pat būtina stebėti, kad eksploatuojant tokį objektą ir numatytais jo avarijų atvejais radioaktyviųjų medžiagų kiekis aplinkoje neviršytų normų. Didelės radiacinės apkrovos regionuose būtina itin daug dėmesio skirti saugumui užtikrinti avarijų bei avarinių situacijų atveju. Analizė atlikta remiantis Archangelsko regiono pavyzdžiu. Išanalizavus 23 tuo atžvilgiu pavojingus objektus, buvo nustatyti ekologijos požiūriu ypač pavojingi. Sukurta metodika ekologinei situacijai įvertinti. Pirmuoju darbo etapu identifikuojami ypač pavojingi radiacijos požiūriu objektai, sumodeliuojama nagrinėjamo regiono radiacinė apkrova. Antrasis darbo etapas ‐ pavojingų objektų avarinių situacijų analizės ir įvertinimo radiacijos požiūriu metodikos tobulinimas.Reikšminiai žodžiai: radiacijos požiūriu pavojingi objektai, avarija, išorinė ir vidinė apšvita, branduolinė ir radiacinė sauga.Экологическая безопасность в условиях радиационних аварий. Анализ и оценка аварийных ситуаций на радиационно опасных объектахАннотация. Риск радиационной аварии на радиационно опасных объектах (РОО) сводится к минимуму в том случае, если техническими и организационными мероприятиями обеспечивается не превышение установленных доз по внутреннему и внешнему облучению персонала и населения, а также норм по содержанию радиоактивных продуктов в окружающей среде при нормальной эксплуатации и проектных авариях. На наш взгляд, в регионах, потенциально подверженных радиационным нагрузка, серьезное внимание должно быть уделено обеспечению безопасности РОО в условиях аварий или аварийных ситуаций. Анализ состояния ядерной и радиационной безопасности в условиях аварий осуществлен на примере РОО Архангельской области. На основе анализа 23 РОО произведена идентификация особо опасных в экологическом отношении радиационных объектов. В связи с этим разработана методика оценки экологической обстановки района в результате авариной ситуации на РОО. На первом этапе методики производится идентификация особо опасных радиационных объектов и моделируется воздействие радиационной нагрузки на исследуемый регион (район). На втором этапе производится анализ и оценка аварийных ситуаций на РОО.Ключевые слова: радиоционно опасные объекты, авария, внутреннее и внешнее обучение, ядерная и радиоционная безопасность.First Published Online: 14 Oct 2010